Zmiana warty w przedsiębiorstwie rodzinnym - ewolucja czy rewolucja - Sułkowski, Łukasz; Marjański, Andrzej (A change of guards in family businesses - evolution or revolution, 2006)
The meaning of family business in economies of countries of the European Union is very large. They constitute, depending on the coimtry, from about 40%-50% (Poland, Italy) to 80% (Germany, Greece) of all companies. The succession, also called intergenerational change management, is a very special and one of most complex problems of family firms. In Poland family businesses developed and gathered significance from the beginning of 1990s. Therefore, most of them have their first succession before them. So, it is worthwhile to use the experience and literature from USA and EU. The article analyses also the most important problems of the succession in family business and considers the issue of whether the process of the succession should take place according to the evolutional model or revolutionary one.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 390-395